Bank Profitability in the case of China - DONG, NINGXUE (2016)
This paper aims at investigating the cost efficiency score and determinants of bank profitability in selected 184 Chinese commercial banks during the period of 2005 to 2015. There are two main methods in this study: The stochastic frontier approach (SFA) and System Generalized Methods of Moments (SGMM). Cost efficiency score will be obtained from SFA, and then as determinants to measure bank profitability. There are bank-specific, industry-specific and macroeconomic determinants to examine bank profitability. Bank-specific determinants involve bank size, credit risk, cost efficiency, capital adequacy, liquidity and insolvency risk. The industry-specific determinant is concentration ratio. Macroeconomic determinants are GDP growth and inflation. According to the results, the variables employed in this paper have different effects on bank profitability.